Bingo: Winning and Losing in the Discourses of Problem Gambling - Fiske, Jo-Anne (Anthropologica, 2015)
This study focuses on how popular discourses of problem gambling construct gendered and racialized identities in central British Columbia, a region producing the highest bingo revenues in the province. It explores how bingo discourses emerge as a symbolic resource within a socio-economic context imbued with a colonial legacy of racialized power relations. The goal is to illuminate, through the application of critical discourse methods, how these discourses legitimate local regimes of power through the pathologizing processes that result in stigmatizing children and women as "bingo orphans," "bingo bags" and "bingo addicts."